Improve Students' Listening Skills by Listening to English Podcasts for Class VIII at Junior High School 4 Mandau - Jufriadi, Jufriadi (International Journal of Business and Information Technology, 2024)
In addressing the problems and difficulties faced by most students in learning listening, several academics and specialists in English teaching decided to pay attention to the most effective approaches, methods and techniques to assist their students in learning listening. This study aims to analyze the effect of using podcasts in the English listening method on students' listening comprehension. The method used is a quantitative method with an experimental research design with pre-test and post-test data collection instruments. The test is taken from the TOEFL IBT. The test consists of six topics with thirty questions. The sample technique used was purposive sampling technique, 30 students of the English Study Program were selected as samples. Data were analyzed statistically using the t-test. . The results of this study show; the students' pre-test average was 27.80 while the students' post-test average was 36.38. After the test results were analyzed, it was found that the average value of the post-test was greater than the average value of the pre-test and showed that the t-count (4.535) was greater than the t-table (2.756), at a significance level of 1%. Thus, the alternative hypothesis is accepted and the null hypothesis is rejected. Based on these results, it can be concluded that the effect of using podcasts in learning English develops students' listening comprehension.